Improving Concentration in ADHD Children with Bowling Game - Naria, Damayanti; Mariyati, Ika Lely (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
This research is based on the results of an initial survey conducted at a kindergarten educational institution which found students with a diagnosis of ADHD in the mild category who have difficulty concentrating. The purpose of this study is to improve the concentration of ADHD children through bowling games. This study used an experimental quantitative method with Single-Subject Research Design (SSRD) technique with A-B-A design. The intervention used is sensory integration therapy with bowling. The data collection method used observation and visual graphs for data analysis. The results showed that there is an increase in concentration in ADHD children after applying bowling games. It indicates that the game is effective in improving concentration in ADHD children. Based on the results of this study, researchers are advised to provide treatment with bowling play therapy for ADHD children.